The Influence of Financial Literacy, Financial Inclusion, Internal Control, and Financial Performance on the Decision to Use QRIS among MSMEs in Medan City - Manalu, Naomi; Panjaitan, Angelina Kisfiyani; Nainggolan, Benny Rojeston Marnaek; Situmorang, Dokman Marulitua (International Journal Of Economics Social And Technology (IJEST), 2025)
This study aims to analyze the influence of financial literacy, financial inclusion, internal control, and financial performance on the decision to use QRIS among MSMEs in Medan City. This research is associative in nature with a quantitative approach. The sampling technique applied is purposive sampling, with a sample size of 95 respondents. Data collection was conducted through the distribution of questionnaires, which were then analyzed using multiple linear regression analysis techniques with SPSS version 25. Based on the research results, the partial analysis shows that: 1) Financial literacy has a significant influence on the decision to use QRIS; 2) Financial inclusion has a significant influence on the decision to use QRIS; 3) Internal control has a significant influence on the decision to use QRIS; 4) Financial performance has a significant influence on the decision to use QRIS. Simultaneously, financial literacy, financial inclusion, internal control, and financial performance collectively influence the decision to use QRIS among MSMEs in Medan City